Child care assistance: Are subsidies or tax credits better? - Xiaodong Gong; Robert Breunig (Institute for the Study of Labor (IZA), 2012)
We evaluate price subsidies and tax credits for child care. We focus on partnered women's labor supply, household income and welfare, demand for formal and informal child care and government expenditure. Using Australian data, we estimate a joint, discrete structural model of labor supply and child care demand. We introduce two methodological innovations: a quantity constraint that total formal and informal child care hours is at least as large as the mother's labor supply and child care explicitly included in the utility function as a proxy for child development. We find that tax credits are better than subsidies in terms of increasing average hours worked and household income. However, tax credits disproportionately benefit wealthier and more educated women. Price subsidies, while less efficient, have positive re-distributional effects.
Keywords: C15; C35; J22; 330; child care; labor supply; elasticities; discrete choice model; Kinderbetreuung; Familienleistungsausgleich; Steuerbegünstigung; Wirkungsanalyse; Weibliche Arbeitskräfte; Arbeitsangebot; Elastizität; Australien